Coffee capsule vending machine / Mohd Sufian Ramli ... [et al.] - Ramli, Mohd Sufian; Abd Wahid, Siti Sufiah; Razak, Muhammad Hasif; Md Said, Muhammad Hakimi (2021)
For a coffee lover, a coffee vending machine is one of the must-have-appliances that should be placed in the public area such as at shopping malls, offices, colleges, and other attractive spots. The machine is the new generation of vending machines that are widely used nowadays, where it is a self-service vending machine. Just follow a few simple steps, insert a coin, choose a flavor and you are done. But the existing vending machine lacks two-way communications especially between the machine itself and the machine's supplier. The suppliers do not have any information about the stocks left in the vending machine. Besides that, the machine user is also exposed to the non-hygienic environment when using the vending machine. The user indirectly needs to touch the vending machine to complete the process. The main objective of this project is to provide a substantial solution to the problems of manufacturing coffee capsule vending machines while keeping it at low costs. The coffee capsule vending machine can be accessed by the supplier using the Internet of Things (IOT) and Bluetooth modules (HC-05) which have been used for wireless communication between smartphone and machine. This machine is also incorporated with infrared sensors for obstacle detection. This project consists of two inputs: an IR sensor and push button and three outputs which are Bluetooth Module (HC05), LCD and servo motor. This Vending machine used Bluetooth module (HC05) as the IOT part. By utilizing the IOT, the information about the stock quantity available inside the machine can be easily obtained. In addition, with this new generation of vending machines it does not need any human interface for every transaction.